2020
DOI: 10.1123/ijspp.2019-0240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postactivation Potentiation on Tennis Serve Velocity and Accuracy

Abstract: Purpose: To examine the postactivation potentiation effect on serve velocity and accuracy in young competition tennis players using complex training, and comparing different upper and lower body heavy-load resistance exercises (HLRE). Methods: Fifteen competition tennis players (9 boys and 6 girls; age 15.6 [1.5] y) performed 1 control session and 3 experimental sessions using HLRE in a crossover randomized design: (1) bench press, (2) half squat, (3) bench press plus half squat, and (4) control trial. HLRE we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
12
2
Order By: Relevance
“…The tennis serve is a technical/tactical skill which plays a critical role in the outcome of a tennis match, and, particularly, ball velocity is a key variable in determining a successful play [44]. We observed that serve velocity increased 1.2% with BJ ingestion, not reaching statistical significance in our study (p = 0.536).…”
Section: Discussioncontrasting
confidence: 76%
“…The tennis serve is a technical/tactical skill which plays a critical role in the outcome of a tennis match, and, particularly, ball velocity is a key variable in determining a successful play [44]. We observed that serve velocity increased 1.2% with BJ ingestion, not reaching statistical significance in our study (p = 0.536).…”
Section: Discussioncontrasting
confidence: 76%
“…Therefore, we can only partially confirm this hypothesis. A previous study has analyzed the effects of physical fatigue on service, without observing significant effects [9]. In contrast, significant positive effects on service have been reported after tennis matches implementing physical recovery protocols [28].…”
Section: Discussionmentioning
confidence: 95%
“…Although speed and accuracy have been shown to be related, few studies have simultaneously analyzed the speed and accuracy of the serve [7,8], or even the relationship between the speed and the accuracy of the serve, taking into account the effect of a physical load on these variables. In this regard, Terraza et al [9] examined the post-activation potentiation effect on serve speed and accuracy in young competition tennis players using high-intensity exercises. They did not find any significant effect of upper and lower body heavy-load resistance exercises on serve accuracy in young competition tennis players.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was probably due to the subjects were asked to hit the ball at maximum velocity, causing more variability in the accuracy and consequently decreasing the reliability. This fact has been observed in tennis [ 16 , 42 ] and dart throwing [ 43 ], though there is some controversy because it has also been observed a positive correlation between velocity and accuracy in tennis [ 44 ].…”
Section: Discussionmentioning
confidence: 95%
“…Despite being two common methods in tennis strength training, which have shown improvements in tennis strokes when trained from 6 to 8 weeks [ 4 , 5 , 12 ] their acute and delayed effects in ball velocity and accuracy in competition tennis players had not been investigated until now. Related to the acute effects, it has not been observed post-activation potentiation effects in tennis serve velocity and accuracy performing complex training by using MB [ 15 ] or RT [ 16 ]. To our knowledge, no more studies investigated the acute effects of strength training in stroke tennis performance and no studies about acute and delayed effects were found.…”
Section: Introductionmentioning
confidence: 99%